Hydro-geophysical characterization and performance evaluation of natural wetlands in a semi-arid wastewater irrigated landscape - Sonkamble, S.; Sahya, A.; Jampani, M.; Ahmed, S.; Amerasinghe, Priyanie H. (Elsevier, 2019)
Natural wetlands are green infrastructure systems that are energy-efficient for wastewater treatment and can be found in diverse geo-environmental settings around the world. Their structure and functions, which defines the treatment efficiencies are highly varied. Wetlands over shallow bedrock and geological lineaments (weak zones) have been known to contribute to groundwater contamination. However, not many studies have been performed to understand the structure in different geological settings to identify the efficiency determining factors. Therefore, it is important to investigate the geological suitability of the natural wetlands. We examined wastewater fed natural wetlands in diverse geological settings aiming at studying the depth, geo-stability, bio-chemical interactions, and hydrogeological attributes that improve the wastewater quality, within the Musi River basin, India. The integrated geophysical scans encompassing electrical resistivity tomography (ERT), hydrogeological test, bathymetric study and hydro-chemical analysis were carried out to explore the physical structure and hydro-dynamic processes in the wetlands. ERT investigations showed that, the depth to bedrock up to 20–25 m devoid of geo-fractures (lineaments) indicated the effective depth of saturated zone as a passable scope for potential bio-chemical interactions, implying the proportionality of the deep seated (deep bedrock) wetland to the pollutant removal efficiency. The lower order of electrical resistivity range 10–35 Om and hydraulic conductivity 2.938 md-1 acquired for saturated weathered zone were found catalyzing the bioremediation, sedimentation, adsorption, redox reactions and ion exchange processes. It caused the deep seated wetland removing nitrate 194.34 kgd-1 (97.18%); sulphate 333.75 kgd-1 (77.70%); phosphate 9.66 kgd-1 (82.53%); microbes 99.99%, BOD 80%, and COD 80% load with discharge 1408 m3d-1 of treated wastewater. Further, the strategies for designating the natural wetlands as wastewater treatment systems are also discussed in this paper.